A feasibility study of a mobile app to treat insomnia. Issue 2 (30th March 2020) - Aji, Melissa; Glozier, Nick; Bartlett, Delwyn; Peters, Dorian; Calvo, Rafael A; Zheng, Yizhong; Grunstein, Ronald; Gordon, Christopher
Abstract: Insomnia is a major public health concern. Sleep restriction therapy (SRT) is an effective behavioral treatment but its delivery is impeded by a shortage of trained clinicians. We developed a mobile app delivering SRT to individuals with insomnia. This feasibility study employed a mixed-methods design to examine the engagement, acceptability, and potential efficacy of the mobile app. Fifteen participants diagnosed with insomnia disorder used the mobile app synchronized with a wearable device for 3 weeks. Those who persisted with the study ( n = 12) found the mobile app to be highly acceptable and engaging, logging on average 19 nightly sleep diary entries across the 21 day period. Significant improvements were observed for sleep measures (insomnia severity and sleep efficiency) and daytime symptoms (fatigue and sleepiness). The results suggest that a mobile app delivering SRT to individuals with insomnia is engaging, acceptable, and potentially efficacious. Further, a full-scale effectiveness study is warranted.